(untitled) (Revista "Boletín el Conuco", 2025)
The objective of this research is to analyze the participation of the autonomous institutions Banco de México and the Federal Competition Commission in the supervision of all financial and economic spheres of public administration, which has favored the elites and privileged economic groups of capital in Mexico from the organization for economic cooperation and development and Banco de México to generate actions that counteract said practices. Documentary analysis was used as a research methodology. The results show that the autonomous bodies Banco de México and the Federal Competition Commission were created to delimit the state’s stewardship in strategic areas. The autonomy of these bodies was compromised from the start, it became clear that their creation had the function of protecting private investment, forgetting that public service companies not only create economic value, but mainly social. Therefore, the importance of citizen supervision is reiterated as the only mechanism of effective pressure that society must ensure that the autonomous bodies comply with the functions they have and pressure their members, in their superior structures, to act. more institutionally and take care of the financial resources they have.